Acoustic micronektonic distribution is structured by macroscale oceanographic processes across 20–50°S latitudes in the South-Western Indian Ocean. (April 2016) - Béhagle, Nolwenn; Cotté, Cédric; Ryan, Tim E.; Gauthier, Olivier; Roudaut, Gildas; Brehmer, Patrice; Josse, Erwan; Cherel, Yves
Abstract: Micronekton constitutes the largest unexploited marine biomass worldwide. It is one of the most conspicuous and ecologically important components of the still poorly known mesopelagic ecosystem. Acoustic data were collected from both fishing and research vessels along 18 transects for a total of 47 682 linear kilometers to investigate large-scale distribution of micronekton over a long latitudinal gradient (20–50°S) and two contrasted seasons (summer and winter) in the South-Western Indian Ocean. Acoustic backscatter at 38 kHz was used as a proxy of mid-water organisms' abundance (0–800 m depth). Two consistent features were diel vertical migration of backscatters and vertical distribution of micronekton in three distinct layers, namely the surface (SL), intermediate (IL) and deep (DL) layers. Satellite remote sensing data was used to position oceanic fronts, and hence define water masses, from the tropical to low Antarctic zones. A key finding of this study was the significant correlation observed between abundance and distribution of acoustic backscatter and position relative to these front and water masses. Total backscatter peaked in the subtropical zone, with low abundances in the colder Polar Frontal Zone. The high overall abundances in subtropical waters resulted mainly from high backscatters in the IL and DL that contrasted with low SL values, especially during the day (2–11%). The warmer the waters, the higher SL backscatter was, with the highest absolute and relative (38–51% of the total abundance) values observed at night in the Tropical Zone and the lowest abundance in the Antarctic Zone. No significant seasonal pattern was found, but SL backscatters were very low in winter compared to summer in the Polar Frontal Zone. Moreover, the Northern winter shift of the fronts induced a Northern latitudinal shift of the peak in abundance from summer to winter. The present study highlights the value of building large acoustic databases collected from both research and fishing vessels. The method provides unique opportunities to gather basic information on micronekton and is an essential step to describe oceanic zones of relevant biological interest in terms of trophic ecology. Highlights: Acoustic data (38 kH) characterizing micronekton were repeatedly collected over 10–800 m depth across a large latitudinal gradient (20–50°S) in the Indian Ocean. A strong correlation was evidenced between spatial distribution of micronekton and macroscale oceanography (water masses delineated by fronts). Micronektonic abundance overall peaked in the subtropics. The vertical structure of micronektonic abundance varied according to water masses. No major seasonal (summer versus winter) difference was found.